An Insight into Value Chains of Green Gram in Bundelkhand Region of India (Indian Journal of Extension Education, 2022)
The study was conducted during 2019-2021 to document the existing value chains of green gram in Bundelkhand region of India. The cost of production estimation showed crop to be profitable for farmers (1:2.61 BC ratio), however, poor uptake (10.9%) of improved varieties among farmers was recorded. An array of value chains actors and their inter linkages were engaged in furthering green gram from producers to consumers through four prominent channels. In addition, a number if enabling factors were observed to support green gram production in the region. Results indicated that producers added highest value to green gram (Rs. 2942.58/q to Rs. 3343.62/q), followed by processors (Rs. 1392.00/q to 2193.65/q) across all marketing channels. Processing component added highest share (29.28 to 35.55%) in total marketing cost across all the channels. Share of producer in consumer rupee for split grains (63.14%) and whole grains (72.78%) was lowest in marketing channel 4 wherein maximum actors were involved. Policy interventions for promotion of green gram producers for aggregation and trading functions need to be taken for them to draw better share in consumer rupee.